(3GdeONd Gdi GdYdhe GdHjFjI (B/s - (3ZQGjHI, SGeMs; (3GdaQMGf, jMjis ((3YeGf(B: s (3OGQ GdTQhb(B, s, 1997)
(3JWhjQ GdYdGbI hGdJaGYd Hjf GdEfSGf hGdHjFI(B- (3eaGgje CSGSjI aj GdHjFI(B- (3GdJZjjQ GdHjFj hCgejJg(B- (3OhQI GdehGO GdHjhLjhcjejGFjI(B- (3GdfXe GdHjFjI GdWHjYjI GdQFjSjI(B- (3GdfXGe GdHjFj GdHTQj(B- (3fhYjI GdHjFI hEOGQJgG(B- (3GdCNWGQ GdHjFjI hJbjje GdBKGQ GdHjFjI(B.s
Keywords: (3GdYdhe GdHjFjIs